Correction: Maksymowicz et al. The Use of Endo-Cellulase and Endo-Xylanase for the Extraction of Apple Pectins as Factors Modifying Their Anticancer Properties and Affecting Their Synergy with the Active Form of Irinotecan. Pharmaceuticals 2022, 15, 732 - Jerzy Maksymowicz; Anna Palko-Łabuz; Beata Sobieszczańska; Mateusz Chmielarz; Mirosława Ferens-Sieczkowska; Magdalena Skonieczna; Agnieszka Wikiera; Olga Wesołowska; Kamila Środa-Pomianek (Pharmaceuticals)
In the original publication [...]